The phylogenetic position of Anacanthorus (Monogenea, Dactylogyridae) parasitizing Brazilian serrasalmids (Characiformes) - Moreira, Juliana; Luque, José L; Šimková, Andrea (Parasite (Paris, France), 2019)
Anacanthorus (Anacanthorinae) is one of the most speciose and common genera of neotropical monogeneans, yet there are still many gaps in our knowledge concerning their diversity and phylogeny. We performed phylogenetic analyses of molecular sequences in order to investigate the phylogenetic position within the Dactylogyridae of Anacanthorus spp. infesting serrasalmids from two Brazilian river basins. Sequences of partial 28S rDNA obtained for nine species of Anacanthorus and Mymarothecium viatorum parasitizing serrasalmids and the published sequences of other members of the Dactylogyridae were included in the phylogenetic reconstruction. Phylogenetic analyses supported the monophyly of anacanthorine monogeneans. The Anacanthorinae (represented in this study by Anacanthorus spp.) formed a monophyletic group included in a large clade together with a group of solely freshwater Ancyrocephalinae and species of the Ancylodiscoidinae. Mymarothecium viatorum (Ancyrocephalinae) was placed within the clade of freshwater Ancyrocephalinae. The phylogenetic analyses indicated that the relationships among species of Anacanthorus reflect those of their serrasalmid hosts: the first subgroup includes a species specific to hosts assigned to Piaractus, a member of the "pacus" lineage; the second subgroup includes a species parasitizing the "Myleus-like pacus" lineage; and the third subgroup includes species parasitizing the lineage of the "true piranhas". We suggest that Anacanthorus and their serrasalmid hosts can be considered a useful model to assess host-parasite biogeography and coevolution in the neotropics. However, future studies focusing on a wider spectrum of host species and their specific Anacanthorus spp. are needed in order to investigate coevolution in this highly diversified system.
Keywords: Sequence Analysis, DNA; Brazílie; druhová specificita; Animals; DNA, Helminth; Phylogeny; Trematoda; nemoci ryb; ribozomální DNA; zvířata; sekvenční analýza DNA; DNA, Ribosomal; DNA helmintů; fylogeneze; Fish Diseases; Species Specificity; Brazil; Characiformes